Aspectos metodológicos de um levantamento epidemiológico rural e descrição das condições periodontais em amostra representativa - Ferreira, Ticiane de Góes Mário (2017)
The oral diseases have a high global prevalence and are a public health problem; however, universal health systems and health policies development need to prioritize them. The epidemiological surveys allow the investigation of the populations’ health status. These studies are considered pivotal to target the oral health goals and to elaborate effective health policies since they present methodological quality. Despite its importance, few population-based surveys with adequate methodologies have been performed to investigate the oral conditions. Thus, this thesis aims to present two articles from an epidemiological study carried out in the rural area of Rosário do Sul, RS, Brazil. The first article describes the methodology used for data collection. It approaches the planning and the participant's selection to obtain a representative sample (subjects ≥15 years) of the region. Additionally, it describes all evaluations performed (oral, clinical, and radiographic examinations; anthropometric measures; gingival crevicular fluid, subgingival biofilm, unstimulated saliva, and blood collections; demographic, economic, medical, and behavioral questionnaires; other questionnaires about alcohol intake, perceived stress, rumination, self-perception of periodontal disease, and oral health impact profile). The second article describes the periodontal status of the representative sample, following recently suggested standards of data reporting. These criteria allow comparisons of the periodontal estimates among different populations and consequently a better understanding of their risk indicators. The response rate was high since 688 individuals (63.3%) were examined. The comparisons with demographic data of the last national census of the Brazilian Institute of Geography and Statistics (2010) validated the sample representativeness. The periodontal disease affected approximately 86% of the individuals, and almost half of the sample presented the moderate form according to the criteria of the Centers for Disease Control and Prevention, in partnership with the American Academy of Periodontology. Forty-nine of 50 people had at least one site with clinical attachment loss (CAL) ≥3 mm, and 74% had CAL ≥5 mm. This survey was carried out with rigorous methodology, aiming to overcome the deficiencies of previous studies, and it provided reliable estimates of periodontal disease. Therefore, it contributed to the knowledge of the periodontal status of a rural area of Rosário do Sul, and it may be used to discuss strategies to improve the health of this population as well as for the development of the health policies. Besides these aspects, this thesis provided data for the global periodontal disease estimates.